Facilitating learner-centered teaching - Rungduin, Teresita Tababa; Rico, Maria Corazon Penetrante; Aggarao, Marivilla Lydia Bulan (Sampaloc, Manila : Rex Book Store, 2022)
"Facilitating Learner-Centered Teaching is a potent tool to help pre-service and practicing teachers understand the fundamental pedagogical principles, processes, and practices that are anchored on learner-centeredness and other educational psychologies, as they apply to facilitate the delivery of teaching and learning in the current educational mullieu. Every chapter also ends with stimulated questions in the Licensure Exam for Teachers. --Provided by publisher
OBE & Outcomes-Based Education --Cover
TEACH series --cover
Includes references (pages 155-157) and index.
Adult
text in English
Keywords: Learning